THE EUROIZATION OF LITHUANIA AND POLAND: A COMPARISON - Czaja, Jaroslaw; Dulkys, Arūnas (Ekonomika, 2012)
Usually, euroization is connected with the necessity of passing through not easy to fulfil and to maintain the Maastricht Treaty criteria and to accept (à) priori a definite course of resigning from the national currency. Upon fulfilling the required adjustment periods of euro adoption, the European law forces a total departure from the national currency. This process is subjected to a solid supervision and control of the EU organs. Additionally, the Maastricht Treaty obliges to introduce the euro when a country is in a good economic condition, confirmed by the fulfilment of nominal convergence criteria. In such a situation, the common currency adoption must be (or should be) always interpreted as a proof of a stable economic development and abilities of keeping such parameters in the future. However, in case of euroization accomplished with omission (or even with infringing) the Treaty, there is no necessity of complementing any European law duties, and especially there is no obligation of totally resigning the national currency. Such kind of euro adoption means not a full but a partial euroization, which can appear in a very difficult situation in country`s economy or when currency independence is not safe and profitable. Resignation from the national currency is like an act of desperation, or at least it is forced by the lack of the abilities to manage the economic problems. The purpose of this publication is to show euroization as state (partly also as process), particularly on the examples of Lithuania and Poland. It obviously it does not seem new, but many changes in the world economy (with special regard to the crisis hurting the European Union) and the lower enthusiasm for joining the Euroland (euro zone) show the need to consider such a problem.